Skew Quadrupole Effect of Laser Plasma Electron Beam Transport - Driss Oumbarek Espinos; Amin Ghaith; Thomas André; Charles Kitégi; Mourad Sebdaoui; Alexandre Loulergue; Fabrice Marteau; Frédéric Blache; Mathieu Valléau; Marie Labat; Alain Lestrade; Eléonore Roussel; et al. (Applied Sciences, 2019)
Laser plasma acceleration (LPA) capable of providing femtosecond and GeV electron beams in cm scale distances brings a high interest for different applications, such as free electron laser and future colliders. Nevertheless, LPA high divergence and energy spread require an initial strong focus to mitigate the chromatic effects. The reliability, in particular with the pointing fluctuations, sets a real challenge for the control of the dispersion along the electron beam transport. We examine here how the magnetic defects of the first strong quadrupoles, in particular, the skew terms, can affect the brightness of the transported electron beam, in the case of the COXINEL transport line, designed for manipulating the electron beam properties for a free electron laser application. We also show that the higher the initial beam divergence, the larger the degradation. Experimentally, after having implemented a beam pointing alignment compensation method enabling us to adjust the position and dispersion independently, we demonstrate that the presence of non-negligible skew quadrupolar components induces a transversal spread and tilt of the beam, leading to an emittance growth and brightness reduction. We are able to reproduce the measurements with beam transport simulations using the measured electron beam parameters.